miR-3174 Contributes to Apoptosis and Autophagic Cell Death Defects in Gastric Cancer Cells by Targeting ARHGAP10 - Bowen Li; Lu Wang; Zheng Li; Weizhi Wang; Xiaofei Zhi; Xiaoxu Huang; Qiang Zhang; Zheng Chen; Xuan Zhang; Zhongyuan He; Jianghao Xu; Lu Zhang; et al. (Elsevier, 2017)
Gastric cancer (GC) is a major health problem worldwide because of its high morbidity and mortality. Considering the well-established roles of miRNA in the regulation of GC carcinogenesis and progression, we screened differentially expressed microRNAs (miRNAs) by using The Cancer Genome Atlas (TCGA) and the GEO databases. We found that miR-3174 was the most significantly differentially expressed miRNA in GC. Ectopic miR-3174 expression was also detected in clinical GC patient samples and cell lines and associated with poor patient prognosis. Apoptosis and autophagic cell death are two types of programmed cell death, whereas both are deficient in gastric cancer. Our functional analyses demonstrated that miR-3174 inhibited mitochondria-dependent apoptosis and autophagic cell death in GC. Moreover, high expression of miR-3174 also resulted in Cisplatin resistance in GC cells. Using bioinformatics analyses combined with in vitro and in vivo experiments, we determined that miR-3174 directly targets ARHGAP10. Notably, ARHGAP10 promoted mitochondria-dependent apoptosis by enhancing p53 expression, which was followed by Bax trans-activation and caspase cleavage. ARHGAP10 also facilitated autophagic cell death by suppressing mammalian target of rapamycin complex 1 (mTOC1) activity. Our results reveal a potential miRNA-based clinical therapeutic target that may also serve as a predictive marker for GC.